Cotton under heat stress: a comprehensive review of molecular breeding, genomics, and multi-omics strategies - Luqman, Tahira; Hussain, Manzoor; Ahmed, Syed Riaz; Ijaz, Iram; Maryum, Zahra; Nadeem, Sahar; Khan, Zafran; Khan, Sana Muhy Ud Din; Aslam, Mohammad; Liu, Yongming; Khan, Muhammad Kashif Riaz (Frontiers in Genetics, 2025)
Cotton is a vital fiber crop for the global textile industry, but rising temperatures due to climate change threaten its growth, fiber quality and yields. Heat stress disrupts key physiological and biochemical processes, affecting carbohydrate metabolism, hormone signaling, calcium and gene regulation and expression. This review article explores cotton’s defense mechanism against heat stress, including epigenetic regulations and transgenic approaches, with a focus on genome editing tools. Given the limitations of traditional breeding, advanced omics technologies such as GWAS, transcriptomics, proteomics, ionomics, metabolomics, phenomics and CRISPR-Cas9 offer promising solutions for developing heat-resistant cotton varieties. This review highlights the need for innovative strategies to ensure sustainable cotton production under climate change.